Effects of different simulated submarine escape depths by free ascent in animal models - Bao, Xiao Chen; Wang, Nan; Xu, Ji; Ma, Jun; Fang, Yi-Qun (Frontiers in Physiology, 2023)
Objective: If a damaged submarine cannot be rescued in time, it is necessary to carry out a submarine escape by free ascent. Decompression illness is the greatest threat to the safety of submariners. The maximum depth at which a safe escape can be carried out is unknown. This study intends to explore the maximum safe escape depth by observing the effects of simulated submarine escape at different depths on animal models. Methods: We evaluated pulmonary function indexes, blood gas values, blood cell counts, the myocardial enzyme spectrum, coagulation parameters, and proinflammatory cytokine levels in rats, electrocardiographic activity in rabbits after simulated 150-m, 200-m, 220-m, and 250-m submarine escape by free ascent. Results: An escape depth of 150 m did not cause significant changes in the indicators. An escape depth of > 200 m led to pulmonary ventilation and gas diffusion dysfunction, hypoxemia, myocardial ischemia, and activation of the fibrinolytic and inflammatory systems. The magnitudes of the changes in the indicators were proportional to escape depth. Conclusion: An escape depth of 150 m in animal models is safe, whereas escape at > 200 m can be harmful.